Kesehatan Reproduksi pada Remaja di Kota Manado: Edukasi Kesehatan pada Siswa SMA - Nelwan, Jeini Ester; Sumampouw, Oksfriani Jufri (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
The increasing prevalence of reproductive health issues associated with risky sexual behaviors and Lesbian, Gay, Bisexual, and Transgender (LGBT) identities among adolescents continues to rise each year. This trend is compounded by the persistently low level of accurate understanding among adolescents regarding these topics. The objective of this community service activity was to provide educational outreach on reproductive health issues for SMAN 6 Manado City students. The activity was carried out by the Community Service (CoS) team, focusing on reproductive health education for students at SMAN 6 Manado City. The implementation of this activity utilized a combination of counseling and mentoring approaches tailored to high school students. The event was conducted on September 20, 2024, starting at 10:00 AM (WIB) until completion, and took place at SMAN 6 Manado City. The educational delivery was conducted through presentations, incorporating both video materials and PowerPoint slides to facilitate understanding. The findings demonstrated a 45-point increase in knowledge scores following the educational intervention. A paired sample t-test indicated a statistically significant difference in students' knowledge before and after the counseling session. The educational intervention had a significant and positive impact on students' understanding of reproductive health.